Bahasa Sebagai Cermin Tengka Pendidikan Masyarakat Madura - Suyyirah Suyyirah; Maimun Maimun; Maysurah Maysurah (ALACRITY : Journal of Education, 2025)
This study aims to analyze the use of bhâsa alos and bhâsa kasâr in the Pasanggar, Pegantenan, Pamekasan community, as a reflection of tengka values (manners and politeness) in social communication. Using a qualitative case study approach, this study involved religious leaders, Islamic boarding school students (santri), youth, and the general public through observation, in-depth interviews, and documentation of daily speech. The results of the study indicate that bhâsa alos functions not only as a means of communication, but also as a means of character building and moral control. The use of polite language is seen as a symbol of honor and politeness, while rude language is used contextually among peers. However, the flow of modernization and social media has caused a shift in tengka values, especially among teenagers, so that norms of politeness in language have begun to fade. Analysis using the Dell Hymes SPEAKING model shows that every element of communication in Pasanggar is based on the values of respect and social balance. Thus, the preservation of the alos language has strategic significance not only for cultural heritage but also as a character education instrument that instills moral, religious, and social values in the lives of Madurese people.